A New Restarting Criterion for FR-CG Method with Exact and Inexact Line Searches - Maha Younis (Al-Rafidain Journal of Computer Sciences and Mathematics)
A new restarting criterion for FR-CG method is derived and investigated in this paper. This criterion is globally convergent whenever the line search fulfills the Wolfe conditions. Our numerical tests and comparisons with the standard FR-CG method for large-scale unconstrained optimization are given, showining significantly improvements.